KEBIJAKAN PUBLIK DAN PELESTARIAN LINGKUNGAN: STUDI EVALUATIF PERDA KABUPATEN AGAM NO. 5 TAHUN 2014 TENTANG PELESTARIAN KAWASAN DANAU MANINJAU - Syarkawi Syarkawi; Ferdi Prayuda (Ensiklopedia of Journal, 2026)
Environmental degradation of Lake Maninjau caused by human activities, particularly from floating net cage (FNC) practices, has resulted in significant ecosystem degradation and has become a concern for the local government. This study aims to evaluate the implementation of Lake Maninjau conservation management policies as stipulated in Agam Regency Regulation No. 5 of 2014 on the Conservation of Lake Maninjau. This study employs a literature review approach based on William N. Dunn's theory of public policy evaluation. The study is qualitative-descriptive in nature, using content analysis methods to examine policy documents, evaluation reports, and relevant academic studies. The results of the study indicate that the implementation of Agam Regency Regulation No. 5 of 2014 on the Conservation of Lake Maninjau has not been optimal. An evaluation of six policy indicators—effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy— These evaluations indicate that the policy faces various structural and social barriers. Dominant inhibiting factors include low public awareness and participation, weak supervision and law enforcement, the absence of zonation in the area, insufficient resource support, and the high socio-economic complexity of the community, which remains dependent on the KJA sector.Keywords: Public Policy;  Environmental Conservation; Policy Evaluation; Lake Maninjau